MARKETING STRATEGY IN QORD –AL HASSAN FINANCING IN SHARIA BANK: STRATEGI PEMASARAN DALAM PEMBIAYAAN QORD –AL HASSAN DI BANK SYARIAH - Ali, Roby; Prayoga, Adistia; Septyo Ginting, Adam (UPMI Proceeding Series, 2023)
In this modern era, Islamic banks have an important role in driving sustainable and inclusive economic growth. One of the financing instruments used by Islamic banks is Qardh Al-Hassan financing, which aims to support social fundraising activities. In this context, an effective marketing strategy is key in increasing public awareness and participation in raising social funds through Qardh Al-Hassan financing. This article will discuss the marketing strategies implemented by Islamic banks in financing Qardh Al-Hassan as well as analyzing case studies on social fundraising.In conclusion, an effective marketing strategy in qardh al-hassan financing can increase public awareness and participation. In addition, the development of product innovation is also important in strengthening the attractiveness of this financing. By implementing a holistic and sustainable marketing strategy, Islamic banks can achieve optimal results in the development of qardh al-hassan financing and social fundraising.